2021
DOI: 10.3389/fneur.2021.629251
|View full text |Cite
|
Sign up to set email alerts
|

Association of Leisure Activities With Cognitive Impairment and Dementia in Older Adults in Colombia: A SABE-Based Study

Abstract: Observational and interventional studies suggest that participation in leisure activities may help protect against cognitive decline in older people. This study aimed to examine the association between participation in leisure activities and cognitive impairment in older adults in Colombia. Data for this study were derived from the Colombian National Survey of Aging (SABE 2015), a cross-sectional survey with a sample size of 23,694 older adults representing the total population (mean age, 70.8 years; 57.3% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Most of the previous studies have investigated individual CR proxies (e.g., education, leisure activity, and social engagement) in middle age or late life in association with cognitive outcomes [26][27][28]. By contrast, our study used the composited CR capacity derived from lifelong cognitively stimulating factors, which could represent the CR capacity accumulated over the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies have investigated individual CR proxies (e.g., education, leisure activity, and social engagement) in middle age or late life in association with cognitive outcomes [26][27][28]. By contrast, our study used the composited CR capacity derived from lifelong cognitively stimulating factors, which could represent the CR capacity accumulated over the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Guerrero Barragán and colleagues’ cross-sectional study of older Colombian adults found that greater participation in cognitive and physical activities in later life was positively associated with cognitive impairment and dementia, independent of literacy and education level. 16 Additionally, frequent participation in leisure activities has also been reported to associate with lowered all-cause mortality among older adults. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Through a prospective study, Ren et al (2022) reported that participation in leisure activities (including keeping domestic animals or pets, taking part in social activities, reading books or newspapers and playing cards, or mahjong) was moderately associated with an increase in cognitive function. An analysis from a national survey including 23,694 older adults also supported that leisure activities functioned as a protective factor against cognitive impairment without dementia and dementia (Guerrero Barragan et al, 2021). Therefore, further studies are needed to clarify the relationships between types of leisure activities and cognitive decline in older individuals.…”
mentioning
confidence: 98%